The impact of the petroleum industry on the economic development of Libya - Parks, Terrance Clinton (Ann-Abor, Michigan : University Microfilms International, 1977)
The purpose of this study is to assess the impact of the petroleum sector on the economic development of Libya
Thesis submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Economics in the Graduate College of the University of Illinois at Urbana-Champaign, 1974
This is an authorized facsimile and was produced by microfilm-xerography in 1977 by University Microfilm International
Includes bibliographical references.
osc 29/01/2019
Ref
Keywords: Petroleum industry; Economic development; Libya